The role of omega-3 in the prevention and treatment of sarcopenia - Dupont, Jolan; Dedeyne, Lenore; Dalle, Sebastiaan; Koppo, Katrien; Gielen, Evelien (Aging clinical and experimental research, 2019)
Sarcopenia is a geriatric syndrome with increasing importance due to the aging of the population. It is known to impose a major burden in terms of morbidity, mortality and socio-economic costs. Therefore, adequate preventive and treatment strategies are required. Progressive resistance training and protein supplementation are currently recommended for the prevention and treatment of sarcopenia. Omega-3 polyunsaturated fatty acids (PUFAs) might be an alternative therapeutic agent for sarcopenia due to their anti-inflammatory properties, which target the ‘inflammaging’, the age-related chronic low-grade inflammation which is assumed to contribute to the development of sarcopenia. In addition, omega-3 PUFAs may also have an anabolic effect on muscle through activation of the mTOR signaling and reduction of insulin resistance. This narrative review provides an overview of the current knowledge about omega-3 PUFAs and their role in the prevention and treatment of sarcopenia. We conclude that there is growing evidence for a beneficial effect of omega-3 PUFAs supplementation in sarcopenic older persons, which may add to the effect of exercise and/or protein supplementation. However, the exact dosage, frequency and use (alone or combined) in the treatment and prevention of sarcopenia still need further exploration.